Prescribing pattern of ophthalmological medication in geriatric inpatients of a tertiary care hospital - A., Sudhindra Prathap; S., Radhika M.; Rai, Reethesh Kumar (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Older people are potentially at greater risk of medication error. Gaining insight into the prescribing pattern especially in eye diseases as they are a common problem in elderly, in order to identify prescribing related problems is the fundamental step in improving the quality of prescription and patient care. Methods: Prescriptions fulfilling inclusion criteria were collected from hospital Medical record department (MRD) and analyzed using the World Health Organization (WHO) core prescribing indicators for rationality of prescriptions. Results: Among 811 prescriptions analysed, 52.7% (428) were of male patients, those aged 60-70 years were 77.2% (626) and patients with only cataract constituted 77% (625). Prescriptions with oral antibiotics were 57.1% (334); topical antibiotics were 35.8% (429) and topical analgesics 46.2% (553). Out of 1182 FDCs noted, 59% (479) were found to be rational and 34.6% (281) were from Essential Medicines List 2014. Only 2% (61) drugs were prescribed using generic name while 64.06% (1606) of drugs were from the WHO Model List of Essential Medicines (April 2015). Average number of drugs per encounter was 3.7. Percentage of encounters with antibiotics was found to be 43.8% and no prescriptions with injections were noted. Conclusions: Although usage of antibiotics and topical drugs was conforming to WHO recommended standards, there is a need to improve prescription pattern by using generic names and drugs from Essential Drug List.